Optimizing Islamic Religious Education Learning through Multi-Method Approaches to Enhance Students’ Learning Interest - Hakiki Fatkhatur Rizqiyah; Rohmatul Izza; Syaikhu Rozi (LifeSciFi, 2026)
Islamic religious education in vocational schools often struggles with low student interest due to reliance on conventional lecture-based methods. This study aims to optimize Islamic religious education learning through the implementation of multi-method approaches to enhance students’ learning interest. This study employed a descriptive qualitative approach, with data collected through in-depth interviews and documentation. The informants included PAI teachers, teaching practicum students, and vocational students. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that the implementation of multi-method approaches, such as project-based learning, audio-visual learning, digital storytelling, and game-based learning, significantly improved students’ learning interest. Students became more engaged, enthusiastic, and active in the learning process. The findings imply that integrating varied and innovative teaching methods can effectively optimize Islamic religious education learning in vocational schools. This approach not only increases students’ interest but also supports meaningful learning experiences and the development of cognitive, affective, and psychomotor domains.